2016
DOI: 10.1521/pedi_2015_29_191
|View full text |Cite
|
Sign up to set email alerts
|

A Dimensional Comparison of a Self-Report and a Structured Interview Measure of Conduct Disorder

Abstract: Eligibility for a diagnosis of antisocial personality disorder (ASPD) requires evidence of antecedent conduct disorder (CD). Accurately identifying CD may be influenced by various factors, including assessment methodology. The present study used a two-parameter latent variable model to examine the relative performance of a self-report measure and a structured clinical interview in retrospectively detecting the CD spectrum among adult male offenders (N = 1,159). Self-report and clinical interview tended to conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…Secondly, the clinical characteristics of the subjects were based on self-perspective data. For CD participants with tendencies to manipulate, deceive or minimize faults, the validity of self-report assessment may be compromised (Kelley et al, 2016). Inconsistent with previous findings, the study observed a lower level of peer problems exhibited by CD participants, which might due to highly positively biased answers given by CD participants.…”
Section: Limitationscontrasting
confidence: 48%
“…Secondly, the clinical characteristics of the subjects were based on self-perspective data. For CD participants with tendencies to manipulate, deceive or minimize faults, the validity of self-report assessment may be compromised (Kelley et al, 2016). Inconsistent with previous findings, the study observed a lower level of peer problems exhibited by CD participants, which might due to highly positively biased answers given by CD participants.…”
Section: Limitationscontrasting
confidence: 48%
“…These different results were caused by variation in participant responses across measures. Shannon et al found that participants with lower severity of disorder may show greater disclosure on anonymous inventories relative to interview formats (55). It might be because of lower defensiveness and fuller reporting of symptoms in the more anonymous paper and pencil setting of a self-report inventory (31).…”
Section: Discussionmentioning
confidence: 99%
“…Research (Auchincloss & Samberg, ; Kelly, Slade, & Grienenberger, ) has shown that the ability to reflect in terms of mental states tends to flow with the skill to regulate one's own emotional states. However, even if this assumption is theoretically reasonable and is often observed in clinical populations (where difficulty in regulating emotion when facing distress is associated with difficulty in understanding others and their behaviors in terms of thoughts), the empirical observation has often produced controversial results (e.g., Kelley et al., ). One one hand, thus, this pattern of findings suggests that the ability to recognize the mental state beyond one's own behavior does not involve also being able to regulate one's own reaction to that circumstance.…”
Section: Discussionmentioning
confidence: 99%